Kinetic asymmetry in female runners with and without retrospective tibial stress fractures - Zifchock, R. A.; Davis, I.; Hamill, J. (Journal of Biomechanics, 2006)
Gait asymmetry may be linked to the tendency for runners to sustain chronic overuse injuries. This paper compares gait asymmetry in female runners who have never sustained a running-related injury to those who have sustained unilateral tibial stress fractures. The symmetry index was used to characterize asymmetry in the kinetics of both subject groups. There were three aims to this study: (1) to report natural levels of asymmetry for healthy, never-injured female runners, (2) to compare asymmetry levels between never-injured runners and those who have sustained stress fractures, and (3) to examine the kinetics between the involved and uninvolved limbs of runners who have sustained stress fractures. In all three aims, peak medial, lateral, braking, vertical impact, and vertical ground reaction forces, average and peak instantaneous vertical loading rates, and peak shock were examined. In the never-injured runner group, natural levels of asymmetry ranged from 3.1% for peak vertical ground reaction force up to 49.8% for peak lateral ground reaction force. Symmetry indices were not significantly different in the runners who had previously sustained stress fractures. The involved limb of the previously injured runners demonstrated higher values for braking and vertical impact ground reaction force and peak shock. Interestingly, these runners appeared to have bilaterally-elevated lateral ground reaction forces and loading rates as compared to the never-injured group, although this was not statistically tested. This suggests that previously injured runners may be closer to the injury threshold and, thus, more susceptible. Asymmetry may simply influence the side on which they become injured.